Brackish water aquaculture: a veritable tool for the empowerment of Niger Delta communities - Anyanwu, P. E.; Gabriel, U. U.; Gabriel, U. U.; Akinrotimi, O.A. (Advances in Aquaculture and Fisheries Management, 2020)
Poverty is generally considered as one of the major causes of food insecurity and poverty alleviation is essential in improving access to food. Among countries in the developing world, including Nigeria, the people in the fishing sectors are some of the poorest and most neglected. This is true of the fishers in the Niger Delta Region of Nigeria. Depletion in natural fish stock, lack of development in the oil rich region, neglect of aquaculture industry have led to disintegration of these traditional communities. Hence, there is massive rural migration to the major cities, especially among the young school leavers seeking for greener pastures. Brackish water fish farming as a profitable alternative venture is a veritable tool that can provide food and jobs for teeming youth and women in addition to freshwater fish and crop farming. The coastal communities of the Niger Delta region has remarkable potentials for the development of brackish water aquaculture, but these remain largely undeveloped not only because of the difficult nature of the terrain, but the government as well as the multinationals have not understood and tapped the potential role of brackish water aquaculture in managing the crisis in the Niger Delta. Economic empowerment of restive youths and women through brackish water aquaculture can be achieved through encouragement of personal investments, formation of farmer cooperative societies provision of loans and credit facilities, on-farm training and establishment of brackish water fish farms by multinationals and government, manpower development in techniques for the propagation and culture of brackish water species such as tilapia, mullet, tarpon, oysters etc at centers like the African Regional Aquaculture Centre, Brackish water Research Station, Buguma, Rivers State. The above if carefully assessed and implemented could go a long way in reducing the tension in the region, thereby making it governable and enhancing economic activities which are gradually grinding to a halt as a result of youth restiveness